2011
DOI: 10.1111/j.1467-8624.2011.01619.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Children With Autism Spectrum Disorders “Hear” a Speaking Face?

Abstract: This study used eye-tracking methodology to assess audiovisual (AV) speech perception in 26 children ranging in age from 5-15 years, half with autism spectrum disorders (ASD) and half with typical development (TD). Given the characteristic reduction in gaze to the faces of others in children with ASD, it was hypothesized that they would show reduced influence of visual information on heard speech. Responses were compared on a set of auditory, visual and audiovisual speech perception tasks. Even when fixated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
131
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(150 citation statements)
references
References 21 publications
18
131
1
Order By: Relevance
“…As opposed to reporting the fused percept, participants with ASDs more often reported the auditory token (compared with TD individuals), a finding also consistent with prior work (Mongillo et al, 2008;Irwin et al, 2011). It is important to note here that differences in illusory McGurk percepts between individuals with and without ASDs could be attributable to differences is either lip reading or impaired face processing, characteristics that have been associated with ASDs (Gelder et al, 1991;Deruelle et al, 2004;Smith and Bennetto, 2007). However, in the current data, such differences would also be seen in visual-only conditions in which the participants are required to both attend faces and read lips, and results from these conditions showed striking similarities across diagnostic groups, reinforcing that the differences are likely the result of atypical multisensory processing.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As opposed to reporting the fused percept, participants with ASDs more often reported the auditory token (compared with TD individuals), a finding also consistent with prior work (Mongillo et al, 2008;Irwin et al, 2011). It is important to note here that differences in illusory McGurk percepts between individuals with and without ASDs could be attributable to differences is either lip reading or impaired face processing, characteristics that have been associated with ASDs (Gelder et al, 1991;Deruelle et al, 2004;Smith and Bennetto, 2007). However, in the current data, such differences would also be seen in visual-only conditions in which the participants are required to both attend faces and read lips, and results from these conditions showed striking similarities across diagnostic groups, reinforcing that the differences are likely the result of atypical multisensory processing.…”
Section: Discussionsupporting
confidence: 86%
“…First, these findings may be applicable in other populations that show atypical temporal processing and multisensory integration, including developmental dyslexia (Hairston et al, 2005;BastienToniazzo et al, 2009) and schizophrenia (Davalos et al, 2002;de Gelder et al, 2003). Second, the link between multisensory temporal processing and multisensory perceptual binding in TD can be seen across but not within studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, developing animals and humans who are deprived of early visual input exhibit neural and behavioral deficits in multisensory integration (36,37). Similarly, children with autism spectrum disorder who tend to pay less attention to people's faces during early development (38) exhibit audiovisual speech integration deficits later in childhood (39)(40)(41).…”
mentioning
confidence: 99%
“…There is currently some debate in the literature about differences in multisensory integration as indexed by McGurk perception. Some groups have found that TD subjects have increased McGurk perception compared with ASD subjects 27,36 , while others have found that ASD subjects had higher McGurk perception 37 . Some of these discrepancies may be explained by differences in the McGurk stimulus used in each study.…”
Section: Representative Resultsmentioning
confidence: 99%